Controlled growth of GaN nanorods directly on flexible Mo metal foil by laser molecular beam epitaxy. (1st June 2020) - Ramesh, Ch.; Tyagi, P.; Gautam, S.; Ojha, S.; Gupta, G.; Kumar, M. Senthil; Kushvaha, S.S.
Abstract: Direct growth of one-dimensional (1D) GaN nanostructures on metal foils is perceived as a promising approach for the realization of futuristic flexible opto-electronic devices. Optimization of growth process to achieve 1D GaN nanostructures on metal foils is a challenging task as the growth is sensitive to the nature of individual metals. Here, we report the laser molecular beam epitaxy growth of GaN nanorods by investigating the role of growth temperature, laser energy density and laser repetition rate in the range of 500–700 °C, 3–5 J/cm 2 and 10–30 Hz, respectively. A higher growth temperature is noticed to be very crucial in determining the formation of 1D GaN nanorod while the laser energy and repetition rate mostly control the nanorod density. GaN nanorod ensemble with the density, length and top cross-sectional width, respectively, 1.41 × 10 9 cm −2, 430–620 nm and 70–160 nm is achieved at 700 °C using laser energy density of 5 J/cm 2 and repetition rate of 10 Hz. The shape of GaN nanorods is nearly same for different laser repetition rates (20–30 Hz) and the density of GaN nanorods increases with the laser repetition rate ( 3.42 × 10 9 cm −2 for 20 Hz and 3.51 × 10 9 cm −2 for 30 Hz). X-ray diffraction, Raman spectroscopy and high resolution transmission electron microscopy studies revealed the c-axis oriented growth of single crystalline wurtzite GaN nanorods on Mo foil. Room temperature photoluminescence spectroscopy exhibited a high intense near band edge emission at 3.4 eV with negligible deep-bands. The controlled growth of self-assembled GaN nanostructures on polycrystalline metal foil with good structural and optical properties has the potential for developing III-nitride based bendable optoelectronic devices.